(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
The life forms of mosses in the forest-steppe zone of Ukraine is discussed. Three life forms (low loose sod, flat carpet, low dense turf) are shown to be dominate within the whole region studied as well in its subprovinces. Some changes (reduction or increase) in biomorphs’ fraction within the subprovinces are explained by special features of regional bryoflora.